Developing Computer-Assisted Tutorial Instructional Program for Teaching Grammar In Higher Education - Untari, Elizabeth Bunga Dwi; *, Ngadiso; Asib, Abdul (Sebelas Maret University, 2016)
The aims of this research were to: (1) gain information on the existing condition of learning media which are used by lecturers to teach grammar, (2) develop the proper media which is suitable for the studentsâ need and appropriate to teach grammar, and (3) find out the feasibility of the proposed media. Research and Development method was used in this research. The research consisted of exploration stage and development stage. Observation, questionnaire, and interview were used to gain the data, while Spiral Data Analysis was used to analyze the data. From the exploration stage, it was found out that the media usually used by the lecturer to teach grammar were Power Point Presentation and handouts. The weaknesses of these media were lecturer dependent, bad presentation, time consuming, non-independent learning, device malfunction, and limited exercises. It was also revealed that Computer Assisted Instruction was not used to teach grammar while it was needed. Moodle based English Grammar Gate was designed as an answer to the studentsâ need. It consisted of two major parts; they are: tutorial part and exercise part. Expert judgment was done to validate the product. The experts suggested several improvements and revision was made regarding the evaluation given. The revised product was then used in field testing to find out the feasibility of the product. Facing two field testing processes and having several revision toward the product, it was then stated feasible.